What Kind of Artificial Intelligence Should We Want for Use in Healthcare Decision-Making Applications? - Wadden, Jordan (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2021)
The prospect of including artificial intelligence (AI) in clinical decision-making is an exciting next step for some areas of healthcare. This article provides an analysis of the available kinds of AI systems, focusing on macro-level characteristics. This includes examining the strengths and weaknesses of opaque systems and fully explainable systems. Ultimately, the article argues that “grey box” systems, which include some combination of opacity and transparency, ought to be used in healthcare settings.